CBCT in orthodontics: a systematic review on justification of CBCT in a paediatric population prior to orthodontic treatment. (22nd October 2018) - De Grauwe, Annelore; Ayaz, Irem; Shujaat, Sohaib; Dimitrov, Simon; Gbadegbegnon, Logan; Vande Vannet, Bart; Jacobs, Reinhilde
Summary: Background: Taking into account radiation doses, safety, and protection, we highlighted the features in which cone-beam computed tomography (CBCT) can offer an advantage compared to the conventional two-dimensional imaging in paediatric dentistry before orthodontic treatment. Objective: The aim of this article was to conduct a systematic review to assess the diagnostic efficacy of CBCT in the paediatric population at a pre-orthodontic phase. Search methods: MEDLINE via PubMed was searched to identify all peer-reviewed articles potentially relevant to the review until 1 July 2018. Relevant publications were selected by two reviewers independently. Selection criteria: The literature selection for this systematic review was carried out according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and was based on predetermined inclusion criteria. Data collection and analysis: Data were collected on overall study characteristics and examination characteristics of the selected studies. Methodological quality of the selected studies was evaluated. Original studies were assessed using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) tool. Thereafter, levels of evidence were obtained according to Grading of Recommendations Assessment, Development and Evaluation criteria. Results: As a result of the QUADAS assessment, a total of 37 articles were included in the protocol. Following a proper protocol, CBCT was regarded as a reliable tool for assessment and management of impacted canine and root fracture. It provided a better evaluation of normal and pathological condylar shape and volume. CBCT was a superior choice for pre-surgical diagnostic applications in cleft lip and/or palate over a medical computed tomography based on its lower radiation exposure, shorter investigation time, and low purchase costs. Conclusions: CBCT is justified only in those cases where conventional radiography fails to provide a correct diagnosis of pathology. Therefore, it cannot be regarded as a standard method of diagnosis. CBCT imaging may also be justified when it positively affects treatment options or provides treatment optimization. Registration: None. Conflict of interest: None to declare.